Clinical profile and deformities in leprosy patients: a record based study - Sanker, Anita; George, Sandhya; Bhaskaramenon, Sindhu Chunangat (International Journal of Research in Dermatology, 2020)
Background: Leprosy is a chronic disease caused by Mycobacterium leprae, infectious in some cases, and affecting the peripheral nervous system, skin and certain other tissues. Even though leprosy was declared eliminated as a public health problem in India on December 2005, new cases of leprosy continue to appear. Hence a study on clinical profile and deformities in all leprosy cases registered in the last 5 years was done to know the current status of leprosy in this area. Methods: This was a retrospective record-based study of leprosy cases done at Government Medical College, Manjeri, for a period of 5 years from October 2014 to September 2019. Results: 42 cases from the record were included in the study. Maximum cases belonged to the age group of 31 to 40 and males were more than females. 81% of the patients were multibacillary leprosy (MB) and 8 cases belonged to paucibacillary (PB) leprosy. Four child cases were registered as PB cases. Mostly encountered clinical diagnosis was borderline tuberculoid leprosy (23 out of 42) and two had type 1 reaction. Seven patients had deformity of which two had grade 2 deformity and rest had grade 1 deformity. Conclusions: One patient who presented with grade 2 deformity and type 1 reaction was from tribal area indicating low awareness about leprosy among them. More number of cases in the multibacillary group and presence of child cases and deformities reinforces the need for strict surveillance to eradicate leprosy.